Analysis of the Utilization of Regional Assets in the Context of Optimizing the Fiscal Potential of the Regional Government of East Java Province - Andi Sujarwo; Ika Devy Pramudiana; Ulul Albab; Widyawati Widyawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze: How is the appropriate technical management of regional assets based on applicable laws and efforts made by the East Java Provincial Government in managing regional assets to optimize Regional Fiscal Potential. This study uses a qualitative method of the Case Study approach. The data collection techniques used in this study are through observation, interviews and documentation. The data was analyzed using an interactive model analysis developed by Miles and Huberman with three procedures, namely data reduction, data display, and conclusion. The results of the study show that the technical management of regional assets carried out by the East Java Provincial Government in managing regional assets in order to optimize Regional Fiscal Potential includes Technical Utilization of Regional Assets in the form of Leases running in accordance with the rules that have been set, this can be seen from the policies used, namely the Governor of East Java Regulation Number 108 of 2018 concerning the Implementation Regulations of the East Java Province Regional Regulation Number 10 of 2017 concerning Management of Regional Property.Technical Utilization of Regional Assets in the Form of Borrowing and Using Property Based on Article 157 of Permendagri Number 19 of 2016, the Implementation of Borrowing and Use is outlined in the agreement and signed by: a.Borrowers and Governors/Regents/Mayors, for regional property that are in the Goods Manageriii; and b. Borrowers and Goods Managers, for regional property that is in the Goods Users. The technical utilization of regional assets in the form of Build to Hand Over / Build to Hand Over is carried out through a Build to Hand Over Agreement / BOT (Bulit Operate Transfer) covering aspects of Civil Law, Land Law (Agrarian), and Administrative Law. The Utilization of Regional Fixed Assets in the Form of Inventory Infrastructure Provision is carried out through SOPs consisting of four, namely; Issuance of Regional Head Decree on Infrastructure Provision Cooperation (KSPI), Selection and Determination of KSPI Partners, Implementation of KSPI and Termination of KSPI. Efforts made by the East Java Provincial Government in managing regional assets to optimize regional fiscal potential, including identification and inventory of the value and potential of regional assets, assessment of regional assets. Supervision and control of asset utilization, Regional asset management information system.